Utilizing Game-Based Learning Baamboozle in Developing Students’ English Grammar Mastery - Sakdiyah, Irma Halimatun; Maolida, Elis Homsini; Nurviyani, Vina (JALL (Journal of Applied Linguistics and Literacy), 2024)
English grammar is one of the essential language elements that students must acquire and master. Unfortunately, mastering grammar is sometimes seen as the most challenging skill to learn among other skills which requires teachers to encourage the students with proper technology so they can optimally learn English grammar. This study aims to find out how students develop their grammar mastery by using game-based learning Baamboozle and investigate the students' responses toward using Baamboozle in developing their grammar mastery. This study applied Classroom Action Research as the research design. This study was conducted in two cycles at one of the Vocational high schools in West Java. The participants of this study were 21 students of class X. Class observations, tests, and questionnaires were used as data collection techniques. The data then were analyzed qualitatively and quantitatively. The result of the analysis shows that students' grammar mastery skills developed, in Cycle I the average score was 72.8 while in Cycle II, the average score was 91.9. The students also responded well to the use of Baamboozle in learning grammar in which they had good perception of activities using game-based learning with the help of Baamboozle. They also actively participated in Bamboozle based grammar activities by actively and voluntarily involving in answering questions. The students admitted that their active involvement was lead by the gamification, interactivity and the competitiveness of the Baamboozle game.